Prasangka Buruk Sebagai Simbol Memakan Daging Bangkai: Tafsir Semiotika Roland Barthes Dalam Surat Al-Hujurat Ayat 12 - Hailen Ike Yunida; Ibnu Alwan Saputra; Naufal Muhazzib; Febriana Istiqomah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This article examines the metaphor of "eating dead brother's flesh" in Surah Al-Hujurat verse 12 using Roland Barthes' semiotic approach to explore the deep meaning contained therein. This letter prohibits prejudice, and through powerful metaphors, depicts such actions as despicable and detrimental to social harmony. Using a semiotic approach, this article discusses the denotative and connotative meaning of the metaphor, as well as how the existing symbols reflect moral values ​​in Islamic teachings. Furthermore, this article explores the relevance of this metaphor in the context of the social and moral challenges facing contemporary society, where prejudice is often spread through social media and digital communications. The conclusion of this study emphasizes the importance of maintaining brotherhood, mutual respect, and avoiding actions that could damage social harmony, as guidelines in dealing with modern social dynamics.